2015
DOI: 10.1080/09593330.2015.1034187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and molar ratio of pollutant to oxidant on a photochemical advanced oxidation process using hypochlorite

Abstract: Ultra violet (UV)-photolysis of hydrogen peroxide (H2O2) is a conventional advanced oxidation process (AOP) and is advantageous in its simplicity, although H2O2 is costly. Accordingly, we tried to substitute H2O2 by hypochlorite in the photochemical AOP, and discussed the effect of pH and the molar ratio of a pollutant to hypochlorite on the process using 1,4-dioxane as a model pollutant. The photochemical treatment of hypochlorite solutions at a wavelength of 254 nm under various pH values revealed that the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Recently, the use of aqueous chlorine and UV as an AOP has been investigated and suggested to be effective in the degradation of recalcitrant organic micropollutants (Watts et al ., 2007; Watts and Linden, 2007; Sichel et al ., 2011; Watts et al ., 2012; Boal et al ., 2015). The UV/Cl 2 process has been suggested as a possible alternative to the UV/H 2 O 2 in the removal of organic micropollutants for several reasons including; (i) the higher UV absorbance and the lower scavenging of HOCl as compared to H 2 O 2 resulting in higher quantum yield (ɸ) during photolysis of aqueous chlorine (HOCl ɸ = 1.4 mol Es −1 and H 2 O 2 ɸ = 1.0 mol Es −1 at 254 nm) (Watts and Linden, 2007; Jin et al ., 2011; Rosenfeldt et al ., 2013; Fang et al ., 2014; Kishimoto and Nishimura, 2015). (ii) The UV/Cl 2 AOP produces three reactive radicals including hydroxyl, chlorine and oxygen radicals (Feng et al ., 2007; Jin et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of aqueous chlorine and UV as an AOP has been investigated and suggested to be effective in the degradation of recalcitrant organic micropollutants (Watts et al ., 2007; Watts and Linden, 2007; Sichel et al ., 2011; Watts et al ., 2012; Boal et al ., 2015). The UV/Cl 2 process has been suggested as a possible alternative to the UV/H 2 O 2 in the removal of organic micropollutants for several reasons including; (i) the higher UV absorbance and the lower scavenging of HOCl as compared to H 2 O 2 resulting in higher quantum yield (ɸ) during photolysis of aqueous chlorine (HOCl ɸ = 1.4 mol Es −1 and H 2 O 2 ɸ = 1.0 mol Es −1 at 254 nm) (Watts and Linden, 2007; Jin et al ., 2011; Rosenfeldt et al ., 2013; Fang et al ., 2014; Kishimoto and Nishimura, 2015). (ii) The UV/Cl 2 AOP produces three reactive radicals including hydroxyl, chlorine and oxygen radicals (Feng et al ., 2007; Jin et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…He also found that light irradiation to chlorine water produced oxygen and hydrochloric acid [4]. Figure 2 shows absorption spectra of hypochlorous acid (HOCl) and hypochlorite ion (ClO − ) [5]. Absorption bands of both species are in the range of UV region, but are quite different each other; HOCl has two absorption peaks at 237 nm with molar extinction coefficient (ε) of 102 M −1 cm −1 and 289 nm with ε of 36.1 M −1 cm −1 , whereas ClO − has a strong absorption peak at 292 nm with ε of 378 M −1 cm −1 and does not show strong absorption around 230 nm.…”
Section: Photolysis Of Chlorinementioning
confidence: 97%
“…However, some researches show that contributions of both HO˙ and RCS increase with a decrease in pH [31,37,40,79]. This discrepancy can be explained by the radical scavenger effect of ClO − [5,16,40,77,79]. Since reaction rate constants of ClO − with HO˙, Cl˙, and Cl 2˙− are higher than those of HOCl (Table 1), the radical scavenging effect of free chlorine is stronger in basic pH than in acidic pH.…”
Section: Effect Of Phmentioning
confidence: 98%
See 2 more Smart Citations